Marketing Processed Agricultural Products in Florida: Steps to Take - Bradley J. Burbaugh; Elena Toro; Amarat H. Simonne; Keith R. Schneider; Renée M. Goodrich-Schneider; Allen F. Wysocki; Arthur A. Teixeira; John T. Fruin (EDIS)
Fruits, vegetables, and other agricultural commodities that are processed, bottled, or packaged for human consumption must be prepared in accordance with statutes enacted by the Florida Legislature and rules administered by the Florida Department of Agriculture and Consumer Services (FDACS). This 6-page fact sheet helps producers understand the rules governing direct marketing in Florida. Written by Bradley J. Burbaugh, Elena Toro, Amarat H. Simonne, Keith R. Schneider, Renée M. Goodrich-Schneider, Allen F. Wysocki, Arthur A. Teixeira, and John T. Fruin and published by the UF Department of Family Youth and Community Sciences, March 2011.